(untitled) (International Journal of Food and Nutritional Sciences, 2022)
ABSTRACT: Flora Nwapa is a pioneer African female writer who blazed the trail in portraying the feminist principles and African cultures in her literary creations. The women lives, problems, and worries with traditional Igbo culture have been significantly explored by Flora Nwapa. It is impacted by British colonization. She want to participate women fully as human beings, not simply in the roles traditionally provided them as wives, mothers and workers, so, she says the women’s demands for change, choice, and acceptance within a community. She examines and analyzes many features in her tribal group. Nwapa’s creative enterprise had a dual task – artistic (contributing to the literary field) and feminist (salvaging the female experience and giving real voices to the women). She was an interesting in writing the novels on women. The disparaging image of women is corrected by her, which is written by male authors. She begins at the bottom, strictly enforced by norms and traditions with masculine supremacy by her female characters in the village enviroment, where gender roles and relationships. This paper presents Igbo Female Voice in the Novels of Flora Nwapa. Efuru (1966), Idu (1970), Never Again (1975), One is Enough (1981), Women are Different (1986) named five novels are used in this paper which is published by Flora Nwapa. The dual burden of women in integrating tradition and modernity in modern-day Nigeria by depicting unyielding heroines, Flora Nwapa expressed the resonance of Oguta Igbo culture.